Análises das não conformidades de tubos de concreto, não armados, destinados a condução de águas pluviais, conforme a NBR 8890/2007 - Birkhahn, Phellipp (2014)
Standardisation of concrete pipes is in charge of the NBR 8890 (ASSOCIATION …, 2007), which defines the parameters to be guaranteed in the final product, with this public and private agencies, are demanding compliance with the notes set forth in this standard. In this paper we analyze concrete pipes, its dimensions, the presence of bubbles, cracks and damaged parts, resistance to diametrical compression of cured and uncured tubes and framing the minimum breaking loads of proposals by the standard, the absorption of concrete employee in the tube and the analysis of possible faults in the production process of the company. Started the studies making the visual and dimensional inspection, it was observed that in the finish there is the presence of surface bubbles that are at odds with the standard also, diametric differences, where there is a greater compression of the extremities. For the verification of the best kind of healing, we used the casing by plastic canvas with 2 variations being casing completely, where the pipe was totally isolated from the elements and the partial casing which was sealed side only, and comparing them with the tubes were exposed to the weather. Tubes that received the casing completely showed superior performance to other types of curing the partially cured tubes had the results that are equivalent to tubes that did not receive healing, thus demonstrating the ineffectiveness of the partial curing system. All tubes showed compressive strength diametrical above the minimum required by the standard, except the pipe with 600 mm diameter that failed this requirement. Absorption is a key factor in the performance in service of this type of pipe, tubes were removed from the walls of the samples and performed the absorption test. Taking into account the maximum allowed absorption, only the tube with a diameter of 400 mm was approved, as the results presented by other samples were varied, not allowing an accurate conclusion. This variation is due to the fact that the same concrete mix is used in all diameters produced by the company, not taking into account their peculiarities, whereas the standard trait was developed for the pipe with a diameter of 400 mm. In order to analyze the variation in the density provided by the radial press, the tubes were weighed and from these results it was found that there is no tube pasta variation and so the packaging provided by the equipment does not demonstrate significant variations as to impair its structure and increase the consumption of concrete. In order to identify possible flaws in the production process was carried out a study of each step that makes up, there were non-conformities in the moisture present in the aggregates, which are not taken into account in the water adding the act in concrete, also found flaws in removal process forms where, by beats cause breaks and cracks that generate in storage and transport. We observed a large drop in pipe ends due to handling, storage, caused by improper handling of the product. For these problems it was suggested that training and specialization of staff.